Under Irish and Foreign Skies: Home, Migration and Regrexit - Kucała, Bożena (Porównania, 2021)
This article analyses literary reflections on the process of migration both from and to Ireland in selected contemporary short stories and poems. Changing Skies (2014), an anthology of stories by Manchester Irish writers, represents a wide spectrum of the Irish migrant experience. Although traditionally perceived as a country which has sent waves of emigrants to other parts of the world, recently Ireland has itself become the destination and adopted home for thousands of immigrants. The second part of the article discusses how foreign writers residing in Ireland view the questions of home, identity and migration in two companion volumes of poetry. The concluding section surveys a sample of Irish writers’ reactions to the process of Brexit, which is redefining migration, home and identity both in Britain and on the island of Ireland, and is causing widespread regret in the Irish community that the tendency towards greater diversity, mobility and heterogeneity has been halted.